Pelajaran dari Reformasi Sistem Birokrasi di Jepang 1945-1952 - Nihei Daisuki; Wahyudi Kumorotomo (Magister Ilmu Administrasi Publik, 1998)
Reforms are usually come out when a country is encountering a crisis. When Japan was totally destructed at the end of World War II, a crisis of identity and public trust to the government, together with the tight supervision and intervention of Allied power under the SCAP (Supreme Commander for the Allied Power), gave all possibilities for the significant economic and political reforms in the country. During the period of Allied occupation in 1945-1952, therefore, Japanese monolithic political system and the strong adherence to the Emperor have been changed into a more democratic and pluralistic system. This fundamental change established a strong basis for Japan to boost economic activities with even higher growth. However, it is proved that administrative or bureaucratic reforms have not been successful during that period. There were still much politicking and vested interests involved in the bureaucratic system which was influenced by hegemonic and crony system. This was because SCAP adopted an